(untitled) (Eurasian Research Bulletin, 2022)
Improving the system of accounting and reporting in the public sector on the basis of international accounting standards, further increase the country’s rating on the basis of adapting the methodological aspects of accounting to the generally accepted names in international practice; increase information coverage and transparency of reports in public finance management; ensuring the integration of financial and statistical reporting; in the context of globalization of international relations, increasing the volume of foreign investment and donor funds.